An In Vitro Effect of Triiodothyronine on Rat Adipose Tissue - Vaughan, Martha (J Clin Invest, 1967)
Triiodo-L-thyronine (T(3)) added in vitro to fat pads from normal, or propylthiouracil-treated rats enhanced the rate of release of glycerol and free fatty acids (FFA) in the presence of epinephrine. An effect of T(3) was also demonstrated in the presence of adrenocorticotropic hormone (ACTH), thyroid-stimulating hormone, or glucagon in studies with tissue from normal rats. The minimal effective concentration of T(3) was approximately 2.5 × 10(-5) mole/liter for intact fat pads and 3 × 10(-6) mole/liter for fat cells. With fat pads from propylthiouracil-treated rats the effect of T(3) was not apparent until the 3rd hr of incubation. Enhancement of epinephrine-stimulated lipolysis by T(3) was evident during the 1st hr of incubation of fat pads from normal rats, and fat cells responded almost immediately to the presence of T(3). When added alone or in the presence of theophylline, 3′,5′-adenosine monophosphate or its dibutyryl derivative, T(3) had little or no effect on lipolysis. The effect of T(3) was observed with or without glucose in the medium, and was not inhibited by cycloheximide or actinomycin D. It did not persist when tissues, after incubation in the presence of T(3) were transferred to medium without T(3). No effect of T(3) on glucose uptake in the presence of epinephrine, ACTH, or insulin was demonstrated.